Factors Related to Perineal Wound Healing in Postpartum Mothers at Jawilan Public Health Center - Euis Nurul Fauziah Suharja; Retno Widowati; Shinta Novelia (Nursing and Health Sciences Journal (NHSJ), 2022)
Based on a preliminary study conducted in the Jawilan Health Center area, from data on deliveries from February to April 2021, there were 173 deliveries, while 50 women gave birth without uterine rupture. Perineal wounds in postpartum mothers that do not heal immediately can cause infection; several factors are known to be associated with the duration of perineal wound healing. This study aimed to determine the factors associated with perineal wound healing in postpartum mothers. This study used an analytic survey, the sampling technique used total sampling and a cross-sectional design. The research instrument contained a questionnaire about five factors of perineal wound healing. The results showed that there was a relationship between perineal wound healing with knowledge (p-value 0.045 <0.05), personal hygiene (p-value 0.035 <0.05), nutrition (p-value 0.000 <0.05), early mobilization ( p-value 0.001 < 0.05). There is no relationship between perineal wound healing and family support (p-value 0.085> 0.05). This study concludes that there is a significant relationship between knowledge, personal hygiene, nutrition, and early mobilization with perineal wound healing.